Strength Training Intensity and Volume Affect Performance of Young Kayakers/Canoeists - Gäbler, Martijn; Berberyan, Hermine S.; Prieske, Olaf; Elferink-Gemser, Marije T.; Hortobágyi, Tibor; Warnke, Torsten; Granacher, Urs (Frontiers in Physiology, 2021)
Purpose: The aim of this study was to compare the effects of moderate intensity, low volume (MILV) vs. low intensity, high volume (LIHV) strength training on sport-specific performance, measures of muscular fitness, and skeletal muscle mass in young kayakers and canoeists. Methods: Semi-elite young kayakers and canoeists (N=40, 13±0.8 y., 11 girls) performed either MILV (70-80% 1-RM, 6-12 repetitions per set) or LIHV (30-40% 1-RM, 60-120 repetitions per set) strength training for one season. Linear mixed-effects models were used to compare effects of training condition on changes over time in 250 m and 2,000 m time trials, handgrip strength, underhand shot throw, average bench pull power over 2 minutes, and skeletal muscle mass. Both between- and within-subject designs were used for analysis. An alpha of 0.05 was used to determine statistical significance. Results: Between- and within-subject analyses showed that monthly changes were greater in LIHV vs. MILV for the 2,000 m time trial (between: 9.16 s, SE=2.70, p<.01; within: 2,000 m: 13.90 s, SE=5.02, p=.01) and bench pull average power (between: 0.021 W·kg-1, SE=0.008, p=.02; within: .010 W·kg-1, SE=0.009, p>.05). Training conditions did not affect other outcomes. Conclusions: Young sprint kayakers and canoeists benefit from LIHV more than MILV strength training in terms of 2,000 m performance and muscular endurance (i.e., 2 min bench pull power).